Entre recreos y retretas. La filarmonía de Tibás - campos, Jafeth (2013)
This study advocates the analysis of the municipal philharmonic band of Tibas, its background, development, organization and disappearance. The Tibas philharmonic band played a determinant role of the community’s social, cultural and educational evolution which made it get support form the neighbourhood, the municipality, the church, the students, the philharmonic band members, and eventually, the State. The importance of this philharmonic band is remarkable. It enriched popular culture for it represented a musical teaching center and a place of sane entertainment for youth. Besides the socializing opportunity, it contributed to bind fraternity and friendship’s joints among Tibas’ community which, at the same time, coadjuted to the strengthening and consolidation of the local identity.